Microorganism-Based Larval Diets Affect Mosquito Development, Size and Nutritional Reserves in the Yellow Fever Mosquito Aedes aegypti (Diptera: Culicidae) - Souza, Raquel Santos; Virginio, Flavia; Riback, Thaís Irene Souza; Suesdek, Lincoln; Barufi, José Bonomi; Genta, Fernando Ariel (Frontiers in Physiology, 2019)
Background: Mosquito larvae feed on organic detritus from the environment, particularly microorganisms comprising bacteria, protozoa, and algae as well as crustaceans, plant debris, and insect exuviae. Little attention has been paid to nutritional studies in Aedes aegypti larvae. Objectives: We investigated the effects of yeast, bacteria and microalgae diets on larval development, pupation time, adult size, emergence, survivorship, lifespan, and wing morphology. Material and Methods: Microorganisms (or Tetramin® as control) were offered as the only source of food to recently hatched first instar larvae and their development was followed until the adult stage. Protein, carbohydrate, glycogen, and lipid were analyzed in single larvae to correlate energetic reserve accumulation by larva with the developmental rates and nutritional content observed. FITC-labeled microorganisms were offered to fourth instar larvae, and its ingestion was recorded by fluorescence microscopy and quantitation. Results and Discussion: Immature stages developed in all diets, however larvae fed with bacteria and microalgae showed a severe delay in development rates, pupation time, adult emergence and low survivorship. Adult males emerged earlier as expected and had longer survival than females. Diets with better nutritional quality resulted in adults with bigger wings. Asaia sp. and Escherichia coli resulted in better nutrition and developmental parameters and seemed to be the best bacterial candidates to future studies using symbiont-based control. The diet quality was measured and presented different protein and carbohydrate amounts. Bacteria had the lowest protein and carbohydrate rates, yeasts had the highest carbohydrate amount and microalgae showed the highest protein content. Larvae fed with microalgae seem not to be able to process and store these diets properly. Larvae were shown to be able to process yeast cells and store their energetic components efficiently. Conclusion: Together, our results point that Ae .aegypti larvae show high plasticity to feed, being able to develop under different microorganism-based diets. The important role of Ae. aegypti in the spread of infectious diseases requires further biological studies in order to understand the vector physiology and thus to manage the larval natural breeding sites aiming a better mosquito control.